(untitled) (HIMALAYA, 2019)
This article focuses on ethnographic work conducted at the Men-Tsee-Khang (Dharamsala, India) on Garuda 5 (khyung lnga), a commonly prescribed Tibetan medical formula. This medicine’s efficacy as a painkiller and activity against infection and inflammation is largely due to a particularly powerful plant, known as ‘virulent poison’ (btsan dug) as well as ‘the great medicine’ (sman chen), and identified as a subset of Aconitum species. Its effects, however, are potentially dangerous or even deadly. How can these poisonous plants be used in medicine and, conversely, when does a medicine become a poison? How can ostensibly the same substance be both harmful and helpful? The explanation requires a more nuanced picture than mere dose dependency. Attending to the broader ‘ecologies of potency’ in which these substances are locally enmeshed, in line with Sienna Craig’s Efficacy and the Social Ecologies of Tibetan Medicine (2012), provides fertile ground to better understand the effects of Garuda 5 and how potency is developed and directed in practice. I aim to unpack the spectrum between sman (medicine) and dug (poison) in Sowa Rigpa by elucidating some of the multiple dimensions which determine the activity of Garuda 5 as it is formulated and prescribed in India. I thus embrace the full spectrum of potency— the ‘good’ and the ‘bad,’ the ‘wanted’ and the ‘unwanted’—without presuming the universal validity of biomedical notions of toxicity and side effects.